PENGEMBANGAN MEDIA KOMIK BERBASIS MODEL STAD PADA PEMBELAJARAN IPAS KELAS V SD NEGERI 32 LUBUKLINGGAU - Hidayaturrokhman; Fauziah, Anna; Rijal, Akmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low interest and learning outcomes of students in Natural and Social Science (IPAS) learning due to the limited use of innovative learning media. The purpose of this study was to develop a comic-based learning media integrated with the Student Teams Achievement Division (STAD) model that is valid, practical, and effective for fifth-grade students of SD Negeri 32 Lubuklinggau. This study employed a Research and Development (R&D) method using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through interviews, questionnaires, and learning outcome tests. Product validity was assessed by language experts, media experts, and material experts using Aiken’s V index. The results indicated that the validity scores were 0.96 from language experts, 0.88 from media experts, and 0.91 from material experts, with an average validity score of 0.92 categorized as highly valid. Practicality results showed percentages of 98% from teachers, 94.67% from one-to-one evaluation, and 94% from small group evaluation, with an average practicality score of 95.56%, categorized as highly practical. Effectiveness testing showed an average pre-test score of 43.48 and a post-test score of 84.92, resulting in an N-Gain score of 0.73 categorized as high. Therefore, the comic-based STAD learning media is considered highly valid, highly practical, and effective for use in elementary school IPAS learning.